Paper chains: tied visas, migration policies, and legal coercion - Niezna, M (Wiley, 2022)
'Tied visa' regimes are labour migration policies that condition migrants' visas on employment with a particular employer, thus restricting their access to the labour market. This article considers how, under such regimes, control by the state shapes control by employers, and investigates the resemblance between official migration control policies and private means of control and coercion, amounting to forced labour and trafficking. The discussion includes the theoretical analysis and empirical consideration of a case study: the Israeli tied visa regime, regulating migrant workers and Palestinian workers. The consideration of two groups of non-citizen workers, subject to different but related regimes, enables a novel analysis of the coercive impact of common labour migration policies, and of the justifications offered for such policies. The Israeli Supreme Court demonstrated some commitment to constitutional principles protecting non-citizens, but later withdrew from these principles and justified tied visas on the grounds that they serve the perceived public interest.